One on one Caloocan blues ; Super 8 [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1990)
Features the controversy between PBA and the PABL regarding the composition of a bastketball team to represent the country in the Beijing Asean Games: the election controversy between OIC Mayor Dr. Martinez and declared winners Macario Asistio of Caloocan: and the TPT featuring their Super 8 Productions with the young aspiring directors.
One on one (18 min.) -- Caloocan blues (14 min. -- Super 8 (13 min.)
VHS.
Keywords: Basketball players -- Philippines; Cinematography; Videorecordings -- Production and direction; Elections -- Corrupt practices. -- Philippines -- Caloocan City; Fraud -- Philippines